Developmentally appropriate pedagogies and training needs among Senior High School teachers in the new normal: a comparative study - Ben Fermin Q Abuda; Kareen Dionesia R Rivera; Jestoni C Orque (International Journal of Humanities and Innovation (IJHI), 2021)
In-service training programs in any organization enable employees to carry out their responsibilities concerning the organizations' standard and effective delivery. In the pandemic, there is an uprising concern among educators on delivering instruction and their readiness to do so. Hence, a descriptive-comparative approach was conducted to investigate senior high school teachers' readiness on developmentally appropriate pedagogies and their training needs. The data was collected using a researcher-developed electronic-based survey instrument through Google Form among 35 senior high school teachers in Dolores National High School. The data analyses include mean computation in assessing respondents' level of academic competence, the median for readiness on developmentally appropriate pedagogies and training needs, and non-parametric Mann Whitney U-test and Kruskal Wallis H-test on the significant difference of teacher readiness when compared according to their academic competence indicators. Findings revealed that the majority of the senior high school teachers possessed low academic competence, were exposed to developmentally appropriate pedagogies on teaching methods and modes of assessment and needed immediate training in managing learners with multiple intelligences and learning styles and provided instruction via electronic or distance learning mode. Also, results revealed a significant gap in the respondents' exposure to developmentally appropriate teaching methods compared to their training acquired (p = .002). Hence, the researcher recommends reviewing schools' in-service training and directing them in preparing senior high school teachers to deliver new-normal-based education.